2018
DOI: 10.3791/56097
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Error-driven Retrieval Procedure for Destabilizing and Rewriting Maladaptive Reward Memories in Hazardous Drinkers

Abstract: Maladaptive reward memories (MRMs) can become unstable following retrieval under certain conditions, allowing their modification by subsequent new learning. However, robust (well-rehearsed) and chronologically old MRMs, such as those underlying substance use disorders, do not destabilize easily when retrieved. A key determinate of memory destabilization during retrieval is prediction error (PE). We describe a retrieval procedure for alcohol MRMs in hazardous drinkers that specifically aims to maximize the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
(80 reference statements)
3
13
0
Order By: Relevance
“…These findings were also in line with the evidence from a study, in which re-association of the alcohol cues with aversion upon alcohol memory retrieval yielded reduction in craving for alcohol in hazardous drinkers (Das et al, 2015;Das et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings were also in line with the evidence from a study, in which re-association of the alcohol cues with aversion upon alcohol memory retrieval yielded reduction in craving for alcohol in hazardous drinkers (Das et al, 2015;Das et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
“…This finding has a critical translational value, as unlike the CPP paradigm, in which exposure to a drug of abuse is short and involuntary (Tzschentke, 2007), operant self-administration procedures are used to model a variety of aspects in addiction (Shaham et al, 2003;Crombag et al, 2008;Everitt et al, 2008;Marchant et al, 2013a;Venniro et al, 2016), including alcohol relapse after prolonged voluntary consumption (Koob, 2000;Burattini et al, 2006;Epstein et al, 2006;Goltseker et al, 2019). Moreover, the retrieval-counterconditioning paradigm is feasible in humans, as it was recently shown that re-association of the alcohol cues with aversion upon alcohol memory reactivation, yielded reduction in alcohol craving in hazardous drinkers (Das et al, 2015;Das et al, 2018).…”
Section: Behavioral Interference With Alcohol Memory Reconsolidation mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous human study used two consecutive days of retrieval-extinction training to decrease craving of abstinent heroin users 14 . Das et al demonstrated that maximizing expectancy violation (prediction error) during memory retrieval before counterconditioning led to a substantial reduction in measures of pre-existing alcohol memories of human hazardous drinkers 15,42 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter involved some form of expectation violation (e.g. generating an expectation that the participant will experience the US, and then violating this expectation; (Das, Gale, Hennessy, & Kamboj, 2018). Table 1, most studies specified the duration of the retrieval procedures used.…”
Section: Retrieval Proceduresmentioning
confidence: 99%